IMPLIKASI VIRAL MARKETING, DESAIN KEMASAN PRODUK, DAN ADVERTISING TERHADAP BRAND AWARENESS PRODUK TEH PUCUK HARUM - Dahlia Nathalia; Novel Reonald; Karisma (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
This study aims to find out about the Implications of Viral Marketing, Product Packaging Design, and Advertising on Brand Awareness of Teh Pucuk Harum Products. The method in this study is quantitative by using the variables Viral Marketing, Product Packaging Design, Advertising, and Brand Awareness. The hypothesis is tested by the F test (simultaneously) and the T test (partially). The population in this study were all users of Teh Pucuk Harum products whose number is unknown in Samarinda City. Sampling from the number of variable indicators was 14 times the maximum number of 10, namely 140 samples. The results of the analysis showed that there was a significant simultaneous influence on the variables Viral Marketing, Product Packaging Design and Advertising on Brand Awareness of Teh Pucuk Harum products, and showed that Viral Marketing had a significant partial effect on Brand Awareness of Teh Pucuk Harum products, Product Packaging Design had a significant partial effect on Brand Awareness of Teh Pucuk Harum products, and Advertising had a significant partial effect on Brand Awareness of Teh Pucuk Harum products.